Patient Attitudes Toward Physician's Assistants - Strunk, Harold K. (1973)
A study was conducted in urban Los Angeles to assess patient acceptance of the use of physician's assistants. Data collection was facilitated by the development of an attitude scale and responses were analyzed to determine differences between various socioeconomic stratifications. With a few exceptions, acceptance was highest among non-married middle-class respondents who have had some exposure to college. As to the perceived complexity of procedures a physician's assistant might perform, 91 percent of all respondents would not object to injections administered by a physician's assistant, but this tolerance diminishes to 34 percent in the case of first examination of a patient by a physician's assistant if there appeared to be a serious head injury.